Performance analysis and engineering application of waste rubber crumbs in concrete - Li Liu (Materials Research Express)
This study experimentally analyzed the impact of rubber particle content and KH-570 pretreatment on the workability and mechanical properties of rubberized concrete, as well as their environmental and economic benefits. The results indicated that the addition of rubber reduced workability, but this was mitigated by KH-570 pretreatment. At a 15% rubber content, pretreated rubberized concrete maintained peak stress similar to the control group, but beyond this threshold, peak stress dropped significantly. Compared to the control, RC25 exhibited a 6.9% increase in peak strain, while KRC25 only showed a 4.3% increase; the secant modulus of RC25 decreased by 46.8%, and that of KRC25 by 34.9%. In terms of toughness, the toughness index of RC25 increased by 15.4%, and KRC25 by 8.3%, demonstrating that rubber enhances concrete toughness, albeit with pretreatment affecting the deformability of rubber particles. KH-570 pretreatment significantly reduced the drying shrinkage of concrete, with a 22.7% reduction after 60 days. Rubberized concrete significantly lowered the CO _2 emissions per unit volume, with RC25 reducing CO _2 E by 61.0% compared to the control group, highlighting the effectiveness of rubberized concrete in reducing carbon emissions associated with concrete production.